Exploring Mathematical Creative Thinking with Design Thinking in Mathematics Learning Innovation - Fauzi Bhustomi; Supandi Supandi; Muhtarom Muhtarom (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to explore innovation in mathematics learning through the application of the design thinking approach to support students' mathematical creative thinking skills. The research employed an exploratory mixed-method approach based on the design thinking framework, focusing on the empathize, define, and ideate stages. The study involved 160 students and 11 mathematics teachers from four madrasahs in Kendal Regency, Indonesia. Data were collected through questionnaires and in-depth interviews and analyzed using descriptive qualitative analysis supported by triangulation techniques. In addition, a meta-analysis of 11 relevant studies was conducted using the OpenMEE application to examine the effectiveness of several proposed learning solutions. The results of the empathize stage showed that 67% of students had positive emotional responses toward mathematics learning, while 65% experienced difficulties in remembering formulas and 57.5% had difficulty understanding mathematical concepts. At the define stage, the main problems identified were students’ difficulties in understanding abstract mathematical concepts, low learning motivation, and the need for more interactive and differentiated learning approaches. The ideate stage generated several potential solutions, including the development of differentiated learning supported by interactive media such as H5P and Edpuzzle as well as the implementation of the REACT learning model. The meta-analysis results indicated a large and statistically significant effect of these learning innovations on improving students' mathematical abilities, with an estimated effect size of 1.683 (p < 0.001; 95% CI = 1.022–2.345). These findings suggest that integrating design thinking with evidence-based learning innovations can provide effective strategies for improving students’ mathematical creative thinking skills and creating more interactive and student-centered mathematics learning environments.